Comparison Between the Most Frequent Fungal Species Colonizing Grapevine Berries at Different Maturation Stages - SAADULLAH, ASIA ABDULHAMID; ABDULLAH, SAMIR KHALAF (Science Journal of University of Zakho, 2013)
The study was undertaken to investigate the most frequent fungal species present on the surface of grape berries at different maturation at vineyards from Duhok governorate, Kurdistan region of Iraq. The associated fungi were detected both before and after surface disinfection on Dichloran Rose Bengal Chlormophenicol agar (DRBC) medium. The most abundant genera and species found on all the three stages of maturation by decreasing orders were Aspergillus (A.niger, A.carbonarius, A.tubingensis), Cladosporium cladosporoides, Penicillium (P.brevicompactum,P.citrinum,P.glabrum), Alternaria alternata and Aureobasidium pullalans. This result support the theory that risk of ochratoxin A contamination can be defined based on the mycobiota present on surface of healthy grape berries.